THE COMPARISON BETWEEN STUDENTS' PHYSICS LEARNING OUTCOMES IN FACE TO FACE (OFFLINE) AND ONLINE LEARNING MODEL - Mohammad Djamil M Nur (Paedagogia: Jurnal Pendidikan, 2022)
This study aims to compare the learning outcomes of physics taught using face-to-face learning models with online learning models at Islamic Senior High School 2 Palu City in the academic year of 2021/2022. In this study, the X1 variable consists of the face-to-face model, the X2 variable is the online learning model, and the Y variable consists of the results of learning Physics. This study used quantitative research with comparative analysis techniques. The subject of the research was students of X IPA 1 at Islamic Senior High School 2 Palu, which is totaling 25 students. Data collection was carried out using student learning outcomes tests, observation, and documentation. The method used for the analysis of hypothesis testing is the paired sample t-test. Descriptive, normality, and homogeneity tests were used for data analysis. The results showed that there were significant differences in the learning outcomes of Physics subjects between face-to-face learning and the online learning model for class X IPA1 Islamic Senior High School 2 Palu in the academic year of 2021/2022. The results of the descriptive analysis calculation show that there is a difference between the Physics Learning Outcomes Taught Using the Face-to-Face Learning Model and the Online Learning Model in class X IPA1 in the academic year 2021/2022. This shows that the face-to-face learning model is more effective than the online learning model in physics subjects.